Perubahan Struktur Pembuluh Xilem Akar Kakao (Theobroma cacao L.) dan Gliricidia sepium pada Cekaman Kekeringan - Prihastanti, Erma - (Bioma : Berkala Ilmiah Biologi, 2010)
Supply of water into leaves depends on the existence of water in xylem. Root system of plants will be affectedfirst if the plants exposed to stress of water shortage. The structure of xylem vessels is an important factor indetermining the presence of embolism induced by drought and varies from one type to another. Research on cocoaagroforestry tree Gliricidia sepium is used as cover crops. The purpose of this study was to analyze changes in thestructure of xylem vessels including area ratio, diameter and hole diameter of cacao root xylem vessels and G.Sepium in drought conditions.Drought stress on the cacao tree and G.sepium performed using EFT systems (throughfall displacementexperiment), which runs from February 2007 - February 2008. Cacao tree used in this study was 5 years old, while6-year-old G.sepium tree. Location of the experiment were divided into six plots comprising three control plots andthree plots roofing. Each plot was taken six and three cacao trees G.sepium tree, where each tree root system wastaken three pieces with diameters of 3-5 mm at 20 cm soil depth.Research results showed that drought stress during 13 months did not affect xylem area ratio, diameter ofxylem cells and xylem vessels, root diameter hole and G.sepium cocoa. However, structural information can beobtained from the root xylem of cocoa have a cell - more xylem cells and pore holes smaller than the root G.sepium.This is shown by the average ratio of the area with an overall area of the root xylem (k) on cocoa roots are ± 0.70while in the root G.sepium ± 0.49. Average diameter of the root xylem cells cocoa ± 1 μ in diameter, length 50-10μm ± vessels and vessel diameter hole ± 0.25 μ. Meanwhile root xylem cells G.sepium shows average diameter ofthe root xylem cells is 1-3 μ, ± 15-25 μ long vessels and vessels holes ± 0.5 μ rang